ISOMORPHOUS CATION DISTRIBUTION IN CELADONITES, GLAUCONITES AND FE-ILLITES DETERMINED BY INFRARED, MöSSBAUER AND EXAFS SPECTROSCOPIES - Drits V.A.; Dainyak L.G.; Muller F.; Besson G.; Manceau A. (My University, 1997)
Celadonite, glauconite and Fe-illite samples were studied by XRD, EXAFS, IR and Mössbauer spectroscopy. The samples were monomineralic and corresponded to 1M polytype. In the OH-stretching region of the IR spectra the content of each definite pair of cations bonded to OH groups was determined. The number of heavy (Fe) and light (Al, Mg) octahedral cations nearest to Fe was found by the EXAFS technique. The predicted quadrupole splitting values for each definite arrangement of cations nearest to Fe 3+ were used to interpret the Mössbaucr spectra. After the fitting procedure, the intensity of each doublet corresponded to a definite set of local cation arrangements around Fe 3+ and to a definite occurrence probability of these arrangements. Computer simulation and the experimental data obtained were used to reconstruct the distribution of isomorphous octahedral cations in the 2:1 layers. For all samples, R 2+ cations prefer to occupy one of the two symmetrically independent cis-sites and R 2+-R 2+ and/or Al-Fe 3+ were prohibited in the directions forming ± 120° with the b axis. Therefore, octahedral sheets of the samples revealed domain structure, in which domains differ in size, in the nature of predominant cation and/or by cation ordering.